REGULATING TEACHING AND PRACTICE OF AESTHETIC MEDICINE AND SURGERY - Noor, Sahibzada Mehmood; Sagheer, Farah (Journal of Postgraduate Medical Institute, 2023)
The practice of Aesthetic medicine and surgery sits across the divide of different specialties; Dermatology and Plastic Surgery in particular. Besides these two specialties Maxillofacial surgery, Ophthalmology, and Otolaryngology also practice aesthetic medicine and surgery. Aesthetic Medicine is evolving as a Specialty in itself globally, and in Pakistan. There is a growing demand for minimally invasive cosmetic procedures (MICPs) including Botox, fillers, chemical peels, and lasers. In 2018, 15.9 million MICPs were performed in the United States, an increase of 228 percent in comparison to the year 2000.1 However, the exact data pertaining to these procedures is lacking in Pakistan. Dermatologists, and to an extent plastic surgeons, are considered more appropriately trained to address the growing demands of a population with aesthetic concerns.2 Besides these two specialties, other specialties and non-medical providers such as aestheticians, nurse practitioners, and physician assistants are providing these services the world over and locally. Accreditation Council for Graduate Medical Education (ACGME) has categorized Dermatologic surgery education into 3 categories: competency, significant exposure, and education. Though competency requires direct training, significant exposure may be achieved through direct observation or assistance, whereas education is defined as available educational material without direct exposure.3 There is no data pertaining to the satisfaction of residents regarding training in Cosmetic Dermatology and aesthetics during residency. However, studies from the West point towards a lack of satisfaction in training.4 Dermatology residency programs in Pakistan offered by the College of Physicians and Surgeons have incorporated mandatory rotations in Lasers and logging of cases at level 2 or observer status. A survey conducted by Asher et. al. amongst Dermatology residents working across Pakistan reported that 65 percent of the participants of the survey wanted to take up Dermatologic Surgery as a subspecialty after completing their fellowship in Dermatology.5 A survey reported that 70% of Canadian residents plan to offer aesthetic services in the future.6 In order, to bridge the gap and train doctors in aesthetic medicine and surgery, there has been a mushroom growth of academies that conduct certificate courses charging the doctors heavily. On top of it, the practice of Aesthetics is costly and mostly conducted in private setups, with minimal regulations. Moreover, there has been a huge unregulated influx of allied healthcare professionals and nonphysician operators (NPOs’), in aesthetic medicine.7 Complications are more common in invasive procedures performed by cosmetic technicians, estheticians, and employees of medical and dental healthcare providers who are not trained for these procedures and there is little or no physician supervision as compared to facilities run by dermatologists Unfortunately, most of institutes imparting education/training in aesthetic medicine offer a short course Thus, after attending a one-day training course, they start performing medical procedures on patients without baseline knowledge and training. The College of Physicians and Surgeons Pakistan recently introduced Fellowship in Paediatric Dermatology as a subspecialty of Dermatology as well as Paediatrics. With the increase in the demand for Aesthetic procedures and practice by multiple specialties, CPSP may introduce a subspecialty in Aesthetics or Cosmetic Dermatology which is under consideration by the Faculty of Dermatology of CPSP. It is the responsibility of various medical and professional associations of relevant specialties, in particular dermatology and plastic surgery, to bridge the gap in teaching for their members in order to regulate the cost and quality of training. The College of Physicians and Surgeons on its part need to expedite the subspecialty programs to address the needs of specialists aspiring to adopt Aesthetic medicine and surgery as a profession. Pakistan Medical and Dental Council (PMDC) should devise regulations pertaining to education as well as the practice of aesthetics in consultation with the College of Physicians and Surgeons and Public sector Universities. The rules and regulations adopted by the PMDC, being the regulatory body, should be adopted by Provincial Healthcare regulatory bodies responsible for overseeing licensing and registration of both public and private sector healthcare establishments to ensure quality, efficiency, and safety in healthcare.